2010
DOI: 10.1186/1756-9966-29-31
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine receptor CXCR7 regulates the invasion, angiogenesis and tumor growth of human hepatocellular carcinoma cells

Abstract: BackgroundIn spite of recent advances in diagnostic and therapeutic measures, the prognosis of hepatocellular carcinoma (HCC) patients remains poor. Therefore, it is crucial to understand what factors are involved in promoting development of HCC. Evidence is accumulating that members of the chemokine receptor family are viewed as promising therapeutic targets in the fight against cancer. More recent studies have revealed that chemokine receptor CXCR7 plays an important role in cancer development. However, litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
118
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(128 citation statements)
references
References 35 publications
(64 reference statements)
8
118
1
1
Order By: Relevance
“…The microarray expression analysis of FAT10 overexpressing NeHepLxHT and HCT116 cells by Gao et al (2014) revealed that the chemokine receptors CXCR4 and CXCR7 were highly up-regulated in FAT10 overexpressing NeHepLxHT cells, consistent with other data showing that NF-B is a transcription factor for both genes (Katoh and Katoh, 2010;Tarnowski et al, 2010). CXCR4 and −7 are both described to promote invasion and tumor growth in several cancer types (Gao et al, 2010;Heinrich et al, 2012;Liang et al, 2005;Zheng et al, 2010). In accordance with these data, an siRNA-mediated knockdown of p65 or overexpression of I B␣ in FAT10 overexpressing NeHepLxHT cells significantly attenuated cell invasion and migration in vitro, precisely as silencing of CXCR4 and CXCR7 did.…”
Section: What Are the Mechanisms Behind Fat10 Overexpression?supporting
confidence: 67%
“…The microarray expression analysis of FAT10 overexpressing NeHepLxHT and HCT116 cells by Gao et al (2014) revealed that the chemokine receptors CXCR4 and CXCR7 were highly up-regulated in FAT10 overexpressing NeHepLxHT cells, consistent with other data showing that NF-B is a transcription factor for both genes (Katoh and Katoh, 2010;Tarnowski et al, 2010). CXCR4 and −7 are both described to promote invasion and tumor growth in several cancer types (Gao et al, 2010;Heinrich et al, 2012;Liang et al, 2005;Zheng et al, 2010). In accordance with these data, an siRNA-mediated knockdown of p65 or overexpression of I B␣ in FAT10 overexpressing NeHepLxHT cells significantly attenuated cell invasion and migration in vitro, precisely as silencing of CXCR4 and CXCR7 did.…”
Section: What Are the Mechanisms Behind Fat10 Overexpression?supporting
confidence: 67%
“…However, the upregulation was not observed in the vasculature of corresponding healthy tissues (12), indicating that angiogenesis is influenced by CXCR7. Hepatocarcinoma cells treated with vascular endothelial growth factor results in a positive feedback for CXCR7 expression (17), further supporting the notion that CXCR7 impacts on vascular growth, therefore favoring precancerosis and subsequently cancerous lesions.…”
Section: Discussionsupporting
confidence: 52%
“…Past report has implied that CXCR7 may play a more critical role in pancreatic cancer progression and prognosis. Shen et al regarded CXCR4 as a key receptor involved in tumor invasion and prognosis, while Liu et al [9] considered CXCR7 to be more important for long term survival in pancreatic cancer patients [9,23,24]. Implications of CXCR7 have been revealed in various tumors, including nervous system, digestive system, endocrine system, genital system, blood system, respiratory system, and urinary system, respectively [9,15,[25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%